Cross-lingual Information Retrieval State-of-the-Art - Nasharuddin, Nurul Amelina; Abdullah, Muhamad taufik (2010)
Information retrieval involves finding some required information in a collection of information or in databases. The information or database need not necessarily be in one language. In other words, language should not limit the finding of information. The way to search for the information is by looking at every item in the collection and when the need to translate the language arises, the techniques and methods developed for the cross-lingual retrieval system is used. This paper reviews some recent researches focusing on topics in cross-lingual information retrieval and their role in current research directions which include new models and paradigms in the wide area of information retrieval.